Peranan Sistem Pengawasan Keuangan Desa Dalam Mendukung Efektivitas Audit - Inggrid Marisca R; Yanuar E Restianto; Laeli Budiarti (AKUNTANSI 45, 2024)
This study aims to determine the role of the Village Financial Supervision System in supporting audit effectiveness at the Inspektorat Daerah Kabupaten Banyumas. This research uses case study qualitative research. The population in this study are 43 users of the Village Financial Supervision System (Siswaskeudes) then a sample of 12 people take using purposive sampling method. Data analysis using qualitative data analysis is the process of selecting, sorting and organizing data that researchers have collect from several sources including field notes, interviews, observations and documentation and the research theory that researchers use is UTAUT and Luder Contigency Model. The results of this study indicate that the role of the Siswaskeudes Application in supporting audit effectiveness at the Regional Inspectorate of Banyumas Regency is to determine priority villages for audits (based on risk analysis), Produce Audit Work Programs and Audit Working Papers automatically and standardized, Audit becomes effective and efficient, easy access to village government financial reports and formulate problem maps as a basis for further action. The driving and inhibiting factors in the use of the Siswaskeudes Application in supporting audit effectiveness at the Regional Inspectorate of Banyumas Regency using the Luder Contigency Model, The stimulant in using the Siswaskeudes Application is the number of villages that must supervise are 74,961 villages but the number of APIP is only 9,124 people. Social Structural Supporting Factors from the user's side, obstacles in Implementation from the user's side of the Siswaskeudes Application including.